Residual stresses of box and I-shaped columns fabricated from S960 ultra-high-strength steel. (March 2020) - Li, Dongxu; Paradowska, Anna; Uy, Brian; Wang, Jia; Khan, Mahbub
Abstract: Ultra-high-strength steel (UHSS) with a nominal yield stress of 960 MPa is of significant interest for the design of heavily loaded compressive members, such as high-rise buildings, long-span bridges and large-scale infrastructure. However, the residual stresses induced by the fabrication process can be detrimental to the structural members. In particular, compressive residual stresses can result in premature buckling and the ultimate strength of fabricated columns will be reduced. To date, research pertaining to the distribution of the residual stresses for UHSS column is limited. An experimental program about the measurements of residual stress distributions for UHSS box and I-shaped columns is therefore presented herein. Measurements of residual stress were undertaken on two box and two I-shaped columns having various width-to-thickness ratios by using the non-destructive neutron diffraction method. The distributions of residual stress in three orthogonal directions for each specimen was measured. The influences of column width-to-thickness ratio on residual stress distributions were investigated and discussed. In addition, simplified analytical models for the box and I-shaped column were established to facilitate the buckling analysis for such UHSS columns. Comparisons of the residual stress distributions between the experimental results and analytical model demonstrated a good agreement and this model can be safely used for the fabricated high-strength-steel (HSS) and UHSS column. Highlights: Residual stresses of box and I-shaped columns fabricated from UHSS plates were measured through neutron diffraction method. Hardness tests were conducted near the welds to ensure the welding quality. Residual stress patterns for box and I-shaped columns were developed based on the previous and current test results. Modified analytical models were proposed for design purposes.